If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 10) + 25 = 0 Reorder the terms: x(10 + x) + 25 = 0 (10 * x + x * x) + 25 = 0 (10x + x2) + 25 = 0 Reorder the terms: 25 + 10x + x2 = 0 Solving 25 + 10x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + x)(5 + x) = 0Subproblem 1
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5Subproblem 2
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5Solution
x = {-5, -5}
| -4(x-5)=12(x+3) | | 6(2x-1)=-11(x+1) | | -2y+3x=2 | | 12x-2y=8 | | 4x+4x=8 | | -9r+5=-28 | | 0.4(y+3)=0.5(y-4) | | 5m+(2m+1)=23 | | 0+50*1-60-60*0+10=10 | | 2+4x=26-x | | 9(m+1)=6m | | 3.49x=78 | | 6x-14=-2x+26 | | x-4=3x-8 | | 3.49+x=78 | | y-2x=6 | | 2x-(4x-12)=3+x | | A+6=22 | | -11*-9= | | 10+1s=30 | | 3+3(2t-3)-3(4t+3)-7= | | -11*9= | | 3+3(2t-3)-(4t+3)-7= | | 6*x=216 | | 5x^2-x-4x^2-12=0 | | -16-4-8= | | -(2y+4)+3(2y+4)-2y= | | ax-b=d-cx | | 4x^4-5x^3-2x^2=0 | | -10+6=-7x+-9 | | 3-4x-5=-2 | | 0.25(12+4x)-0.5(8+2x)=0 |